Elements influencing the success of Human Resource Information System - Dinusha Dissanayake; Nandasena Nandasena (Annals of Management and Organization Research, 2019)
Purpose: Due to the upgrade of technology, it has swapped the methods of controlling human beings in companies. In this context, finding the elements influencing the success of the HRIS in ABC manufacturing (Pvt) Ltd was the current research motive. Research methodology: The study design was deductive and quantitative. Moreover, primary data with Scale questionnaire was utilized for data gathering. 30 executives were selected in ABC manufacturing (Pvt) Ltd have directly dealt with the HRI System. Further, data analysis did through regression analysis. Results: The results confirmed that the success of HRIS was significantly impacted by the internal environmental elements and the external environmental elements. Also, found that internal environmental factors have the highest influence on the success of HRIS compared with the rest. Limitations: The respondents chosen for the study were 30 in one single company. Instead, the researcher selected two determinants only. Contribution: The researcher is motivated through this study because electronic, personal applications are now highly concern in local companies. The research findings can apply to organizations in third-world profiles to boost their HRI systems' efficacy. Keywords: Human Resource Information System (HRIS), Internal environmental elements, External environmental elements